GLOBALIZING UZBEKISTAN'S SMALL BUSINESSES: PROSPECTS AND OPPORTUNITIES - Dilmurod Oripov (European Science Publishing, 2024)
This article delves into the prospects for the development of small businesses in Uzbekistan within international markets. It examines the key success factors, challenges, and opportunities that Uzbekistan's small and medium-sized enterprises (SMEs) face in the context of globalization and economic integration. By analysing the current landscape, this study highlights the strategic measures needed to enhance the global competitiveness of Uzbek SMEs. The discussion focuses on the importance of innovation, market diversification, and supportive governmental policies as pivotal elements in fostering international growth. Through a comprehensive exploration of these aspects, the article aims to provide valuable insights into how Uzbek small businesses can effectively navigate and thrive in the global market.
Keywords: small business, international markets, export, innovation, competitiveness, government support, training, infrastructure, international cooperation.